The Role of the Husband in Supporting His Wife Post-Childbirth from A Christian Perspective - Manggi, Nelci Oktavianti (Scriptura Indonesia, 2025)
The postpartum state requires important accompaniment from the husband. Before and after childbirth the wife experiences psychological changes that can cause depression. If the wife is depressed, she cannot concentrate on taking care of the children. It will also cause trauma to the wife and children. Even children will not grow and develop according to their age. The writing method uses a qualitative approach by conducting interviews and literature reviews through books, journals that are relevant to the research topic. The role of the husband is not only to meet the needs of the wife and children materially but to love and love the wife is the main thing in a Christian family. Feelings of love and love are the main needs for the wife. The wife will feel calm and happy and will be more focused on taking care of the children and household.